2012
DOI: 10.1080/15374416.2012.651994
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Association Between Cognitive Functioning and Anxiety in Children With Autism Spectrum Disorders: The Role of Social Understanding and Aggression

Abstract: This study examined relations between anxiety, aggression, social understanding, IQ, and diagnosis in a sample of 231 children (ages 2-9) diagnosed with Autism Spectrum Disorders (ASDs; Autistic Disorder, Asperger's Disorder, Pervasive Developmental Disorder Not Otherwise Specified) in a hospital setting. Children were administered tests of IQ, and parents completed measures of remaining variables. ASD diagnosis was associated with level of anxiety, and level of IQ explained this relation. IQ was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 48 publications
0
29
2
Order By: Relevance
“…Few studies have looked at the relationship between anxiety and adaptive function, with high anxiety related to lower IQ in typical populations [27], but this is not the case in some developmental disorders such as autism, where higher anxiety is found in those with high IQ [28]. Our findings indicate that in 22q11.2DS, anxiety may affect individuals across all levels of cognition, thereby suggesting other modulatory factors such as environmental demands.…”
Section: Discussionmentioning
confidence: 71%
“…Few studies have looked at the relationship between anxiety and adaptive function, with high anxiety related to lower IQ in typical populations [27], but this is not the case in some developmental disorders such as autism, where higher anxiety is found in those with high IQ [28]. Our findings indicate that in 22q11.2DS, anxiety may affect individuals across all levels of cognition, thereby suggesting other modulatory factors such as environmental demands.…”
Section: Discussionmentioning
confidence: 71%
“…This suggests that the direction of effect for dysregulation of aggression may be species specific. Alternatively, the difference may relate to a qualitative difference in aggression toward a stranger as opposed to a familiar individual: the resident–intruder assay measures the aggressive (and other) behavioral response to an intruder entering the home cage of the resident, whereas the majority of reports of increased aggression in ASD are toward teachers and/or caregivers (e.g., Hartley et al ; Lecavalier ; Lecavalier et al ; Maskey et al ) or unspecified targets (e.g., Holden & Gitlesen ; McDougle et al ; Niditch et al ; Robb ). Some studies have found that the presence of a stranger leads to minimal social interaction (Hobson & Lee ; Lord ) and increased stereotypic, repetitive behavior (Hutt & Hutt ), which is consistent with our current findings that Pten +/− mice showed decreased social interaction and aggressive behavior and increased repetitive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, male Pten +/− mice were less anxious than their Pten +/+ littermates (Clipperton‐Allen & Page ). Aggression has been associated with anxiety in humans with (e.g., Niditch et al ; Pugliese et al ) and without ASD (e.g., Frick et al ; Hatfield & Dula ; Marsee et al ; Sareen et al ; Tsiouris et al ), and it has previously been suggested that more aggressive male mice may also be more anxious (Ferrari et al ; Guillot & Chapouthier ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, participants with both high and low levels of empathy had lower levels of self‐reported anxiety symptoms [Bellini, ]. In contrast, Niditch, Varela, Kamps, and Hill [ ] examined the relationship between social understanding and anxiety in a large group of children with an ASD (n = 231), both measured via the parent rating scale from the Behavior Assessment System for Children‐2 [Reynolds & Kamphaus, ]. Results indicated that greater social understanding was significantly correlated with higher anxiety [Niditch et al., ].…”
Section: Social Cognition In Asd Anxiety and Depressionmentioning
confidence: 99%